Studi Docking Molekular Senyawa Turunan Kuinolin Terhadap Reseptor Estrogen-Α - Mohammad Rizki Fadhil Pratama (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
Estrogen-α (ER-α) is the main target for ER + therapy. Inhibition of ER-α is known to slow the proliferation of ER + breast cancer cells. Quinoline derivatives are known to have anticancer activity by inhibiting several types of receptors. It is not known whether quinoline can inhibit ER-α. This study aims to determine the interaction between ER-α with quinoline derivative compounds. Molecular docking of ER-α showed that quinine gave the most negative bond-free energy and the smallest inhibition constant, respectively -8.73 kcal/mol and 0.398 μM. These results provide predictions that quinine has activity as an ER-α inhibitor and has the potential to be developed in the treatment of ER + breast cancer. However, the affinity shown by quinine was lower than that of 4-hydroxytamoxifen, a potent inhibitor of ER-α.